Centrifugal colectomy. Oncological isolation - Suiffet, Walter (Cirugía del Uruguay, 1971)
The author refers to the evolution of surgical techniques in right colectomies of cancer. The conceptual evolution of the technique is analyzed from the point of view of profilaxis of tumoral diffusion. This is based on protection of tumor, luminal and vascular blocking, mobilization and ultimately, resection of tumor. This is aimed at avoiding peritoneal grafts, luminal grafts, lympho-venous diffusion and parietal grafts. The surgical technique is analyzed in all its stages and illustrated in a semischematic manner. It has been employed by the author for the last 10 years. Basic bibliographic references are included.